Iron overload in Plasmodium-infected placenta as a pathogenesis mechanism of fetal death - Carlos ePenha-Gonçalves; Raffaella eGozzelino; Luciana Vieira de Moraes (Frontiers Media S.A., 2014)
Plasmodium infection during gestation may lead to severe clinical manifestations including abortion, stillbirth, intrauterine growth retardation and low birth weight. Mechanisms underlying such poor pregnancy outcomes are still unclear. In the animal model of severe placental malaria (PM), in utero fetal death frequently occurs and mothers often succumb to infection before or immediately after delivery. P.berghei infected erythrocytes (IEs) continuously accumulate in the placenta, where they are then phagocytosed by fetal-derived placental cells, namely trophoblasts. Inside the phagosomes, disruption of IEs leads to the release of non-hemoglobin bound heme, which is subsequently catabolized by heme oxygenase-1 (HO-1) into carbon monoxide, biliverdin and labile iron. Fine-tuned regulatory mechanisms operate to maintain iron homeostasis, preventing the deleterious effect of iron-induced oxidative stress. Our preliminary results demonstrate that iron overload in trophoblasts of P. berghei-infected placenta is associated with fetal death. Placentas which supported normally developing embryos showed no iron accumulation within the trophoblasts. Placentas from dead fetuses showed massive iron accumulation, which was associated with parasitic burden. Here we present preliminary data suggesting that disruption of iron homeostasis in trophoblasts during the course of placental malaria is a consequence of heme accumulation after intense IE engulfment. We propose that iron overload in placenta is a pathogenic component of PM, contributing to fetal death. The mechanism through which it operates still needs to be elucidated.